A genome‐scale CRISPR knock‐out screen in chronic myeloid leukemia identifies novel drug resistance mechanisms along with intrinsic apoptosis and MAPK signaling - Matthieu Lewis; Valérie Prouzet‐Mauléon; Florence Lichou; Elodie Richard; Richard Iggo; Béatrice Turcq; François‐Xavier Mahon (Cancer Medicine, 2020)
Abstract Understanding resistance mechanisms in cancer is of utmost importance for the discovery of novel “druggable” targets. Efficient genetic screening, now even more possible with CRISPR‐Cas9 gene‐editing technology, next‐generation sequencing and bioinformatics, is an important tool for deciphering novel cellular processes, such as resistance to treatment in cancer. Imatinib specifically eliminates chronic myeloid leukemia (CML) cells by targeting and blocking the kinase activity of BCR‐ABL1; however, resistance to treatment exists. In order to discover BCR‐ABL1 independent mechanisms of imatinib resistance, we utilized the genome‐scale CRISPR knock‐out library to screen for imatinib‐sensitizing genes in vitro on K562 cells. We revealed genes that seem essential for imatinib‐induced cell death, such as proapoptotic genes (BIM, BAX) or MAPK inhibitor SPRED2. Specifically, reestablishing apoptosis in BIM knock‐out (KO) cells with BH3 mimetics, or inhibiting MAPK signaling in SPRED2 KO cells with MEK inhibitors restores sensitivity to imatinib. In this work, we discovered previously identified pathways and novel pathways that modulate response to imatinib in CML cell lines, such as the implication of the Mediator complex, mRNA processing and protein ubiquitinylation. Targeting these specific genetic lesions with combinational therapy can overcome resistance phenotypes and paves the road for the use of precision oncology.